1989
DOI: 10.1093/ajcn/50.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Energy supplementation in the last trimester of pregnancy in East Java, Indonesia: effect on breast-milk output

Abstract: Breast-milk output was measured in women who during the last trimester of pregnancy consumed a high- or low-energy supplement (53 and 55 women, respectively). Infant and mother pairs were enrolled at 2 or 6 wk postpartum. Test weighings were done four times at 8-wk intervals. Mean breast-milk output ranged from 682 to 744 g/d in the age period of 2 wk to 7 mo. There was no difference in milk output between the two experimental groups. In all cohorts, breast-feeding frequency influenced milk output positively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Milk-output of these underprivileged mothers was not influenced by the supplement or the duration of the supplementation. These results are in accordance with previous studies conducted in the Gambia [26,27], Indonesia [25], and Kenya [22], supporting a lack of association between supplementation and breastmilk output.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Milk-output of these underprivileged mothers was not influenced by the supplement or the duration of the supplementation. These results are in accordance with previous studies conducted in the Gambia [26,27], Indonesia [25], and Kenya [22], supporting a lack of association between supplementation and breastmilk output.…”
Section: Discussionsupporting
confidence: 93%
“…Despite its importance for public health, the question of whether poorly nourished women can improve their lactation performance when increasing their dietary intake was conflicting [19]. Several studies in developing countries have reported a positive or no relationship [19][20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial in Indonesia in 1982 measured the impacts of a protein‐energy beverage containing palm oil and sunflower oil (both low in omega‐3 fatty acids), high or low amounts of casein and glucose without micronutrient fortification during pregnancy on birthweight and breast milk output (Kardjati et al . 1988; van Steenbergen et al . 1989).…”
Section: Formulated Protein‐energy Drinksmentioning
confidence: 99%
“…Out of the 54 excluded studies, 13 were on BEP supplementation (Anonymous, 1995 ; Blackwell et al, 1973 ; Devi et al, 2017 ; Hawkesworth et al, 2011 ; Kardjati et al, 1990 ; Kusin et al, 1992 ; Mueller & Pollitt, 1984 ; Rush et al, 1980 ; Saville et al, 2018 ; van Steenbergen et al, 1989 ; Wang et al, 2015 ; Winkvist et al, 1998 ; Zhang, 1997 ). Three studies (Anonymous, 1995 ; Wang et al, 2015 ; Zhang, 1997 ) were excluded due to their wrong patient population of interest; three were excluded due to missing standard of care control group (Kusin et al, 1992 ; van Steenbergen et al, 1989 ; Winkvist et al, 1998 ), and two studies were excluded due to wrong intervention as they provided BEP along with micronutrient supplementation (Devi et al, 2017 ; Saville et al, 2018 ). Zhang ( 1997 ) only included IUGR births, Wang et al ( 2015 ) only included women suffering from GDM, and Anonymous ( 1995 ) did not exclusively include pregnant women.…”
Section: Resultsmentioning
confidence: 99%